SOCIO-ECONOMIC IMPACT OF THE INTERNATIONAL CATTLE MARKET IN MUBI SOUTH LOCAL GOVERNMENT, ADAMAWA STATE NIGERIA - Yahaya, Adamu (International Journal of Research -GRANTHAALAYAH, 2018)
The study examined the social and economic contribution of Mubi Cattle Market to the economy of Mubi South Local Government Area. The study data were primarily sourced from the market through structured questionnaire and interviews. The Result obtained revealed on average, 5000 – 7000 cattle are sold in the market on weekly basis where N250 is paid per cattle as revenue to the state and local government (N150 and N100 respectively). It further revealed that about 40% of the revenue collections within the local government emanates from the market, making the market the biggest source of revenue for the local government. Youths are gainfully employed by running various businesses apart from the livestock business in the market. Most of the respondents fall within the age bracket of 20 – 45 years. The result also shows that although the market contributes about 40% of revenue generated within the local government, more revenue could still be generated if sellers of other products such as shoes, clothes, food, and robes etc. were to be taxed. Major challenges of the market included insecurity, language barrier and the non-willingness of some of the marketers to pay tax. It is therefore recommended among other thinks that government should provide a strong communication system, rehabilitate bad roads, and enhance security measures and consciousness for the sustenance of this informal sector employment and revenue generating business.